O circuito inferior da economia urbana em São Miguel dos Campos/AL no período técnico-científico-informacional - Silva Neto , Antônio Lopes da (2016)
The objective of this labor in comprehend the urban economic of São Miguel dos Campos-AL in the period technico-scientific-informational from activities of lower circuit of urban economy, and to analyze the use of agentes as well as to analyze uses of the territory by the small agents of economy. The theory about the two circuit of economy proposal by Milton Santos (2008, [1979]), comprehend important bias theoretical and methodological to the understand of urbanization in the underdeveloped countries. The lower circuit of economy is formed by existing set of small activities in the city. Generally meeting the labor needs and consumption of the urban poor. We choose the situation of São Miguel dos Campos-AL. And to understand the dynamic of your urbanization, we analyzed your characteristics, organization and the operation of three activities of lower circuit of economy: the micro and small companies, the urban passenger transport and the free fair of São Miguel dos Campos. The understanding these activities in addition to revealing the uses of the territory of the city, They feature the major part of poverty of the urban population and indicate the need for solving them in the current period.